Effects of supplementation with branched chain amino acids and ornithine aspartate on plasma ammonia and central fatigue during exercise in healthy men - Mikulski, Tomasz; Dabrowski, Jan; Hilgier, Wojciech; Ziemba, Andrzej; Krzeminski, Krzysztof (Folia Neuropathologica, 2015)
Introduction : Our previous studies showed only slight improvement in central fatigue, measured indirectly by psychomotor performance, after branched chain amino acids (BCAA) supplementation during various efforts in healthy men. It is hypothesised that hyperammonaemia resulting from amino acids metabolism may attenuate their beneficial effect on psychomotor performance; therefore, the L-ornithine L-aspartate (OA) as an ammonia decreasing agent was used. The aim of this study was to investigate the effectiveness of oral BCAA + OA supplementation to reduce plasma ammonia concentration and enhance psychomotor performance during exhaustive exercise in healthy men. Material and methods : Eleven endurance-trained men (mean age 32.6 ± 1.9 years) performed two sessions (separated by one week) of submaximal cycloergometer exercise for 90 minutes at 60% of maximal oxygen uptake followed by graded exercise until exhaustion with randomised, double-blind supplementation with a total of 16 g BCAA and 12 g OA (BCAA + OA trial) or flavoured water (placebo trial). Before exercise, during both efforts and after 20 minutes of recovery multiple choice reaction time (MCRT), perceived exertion, heart rate and oxygen uptake were measured and venous blood samples were taken for plasma leucine, valine, isoleucine, ornithine, aspartate, free tryptophan (fTRP), ammonia, lactate and glucose determination. Results : After ingestion, during both efforts and after 20 minutes of recovery the plasma concentrations of all supplemented amino acids were significantly increased, while the fTRP/BCAA ratio decreased in the BCAA + OA trial more than in the placebo trial. At the end of graded exercise plasma fTRP was lower and MCRT shorter in BCAA + OA than in the placebo trial (p < 0.05). At the end of prolonged exercise the plasma ammonia concentration was higher in BCAA + OA than in placebo trial (p < 0.05). Decreases in plasma ammonia during recovery were significantly higher in BCAA + OA than in the placebo trial. Plasma ammonia positively correlated with the total plasma BCAA and MCRT only in the BCAA + OA trial. The fTRP/BCAA ratio positively correlated with MCRT only in the placebo trial. Conclusions : Supplementation with BCAA and OA is a useful way to improve MCRT during high-intensity exercise and accelerate the elimination of ammonia at the recovery stage after exercise in healthy young men.